Analysis of 20th Century Nusantara Interpretation (Al-Bayan Interpretation by T.M. Hasby Ash-Shiddieqy) - Nurul Hartini; Fitria; Pebrina; Ayu; Widya; Nurul Khoiria; Hanum; Arif Saman; Abdul Rahman; Akbar; Salahuddin Harahap (Penerbit Hellow Pustaka, 2025)
Tafsir Al-Bayan, a work of interpretation of the Qur'an produced by a person named M. Hasby Ash-Shiddieqy which was published in 1966 AD. This work is one of the prominent examples of Indonesian tafsir in the 20th century, which seeks to bridge the understanding of Al-Bayan. -Qur'an through the social and cultural realities of Indonesian society. This article will examine the distinctive characteristics of Tafsir Al-Bayan, such as the use of Indonesian that is easy to understand, the emphasis on moral and social values, and the relevance of the message of the Al-Qur'an to the lives of Indonesian people.